Water law, poverty, and development water sector reforms in India - Cullet, Philippe (Oxford : Oxford University Press, 2009)
This monograph examines water law regulations and reform in the present decade, going beyond a simple analysis of existing water law and regulations to encompass environmental, social, economic, and human rights aspects of water as a natural resource.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Water-supply -- Law and legislation; Water resources development -- Law and legislation; Water rights (International law); Water resources development -- India -- Case studies; Water resources development -- Law and legislation -- India